(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The king of all diseases diabetes has become a global health issue affecting >170million people worldwide. It is the leading causes of death and disability in human beings. By 2030 it is estimated rise to 366 million. Type II Diabetes (T2D) accounts to 90 of the diabetes cases globally, caused by impaired insulin secretion from pancreatic beta cells and insulin resistance of the peripheral target issues, especially muscle and liver. Clearly, T2D has become an epidemic in the 21st century where India leads the world with largest number of diabetic subjects. Traditional medicines are obtained from medicinal plants and are used by about 40-60 of the world’s population. Though there are many approaches to control diabetes and its secondary complications, herbal formulations are preferred due to lesser side effects and low cost. Stevia rebaudiana and Phyllanthus amarus are medicinal plants for the potential management of diabetes mellitus. The leaves are used in herbal medicinal preparation. The concerned study reveals the anti-diabetic potential of Stevia rebaudiana and Phyllanthus amarus in controlling blood glucose level in Streptozotocin induced Diabetic rats. Steviosides of Stevia rebaudiana and lighans, galloatnoids of Phyllanthus amarus may be responsible for the significant stimulation of β-cells of pancreas in the production of Insulin. In the current work we have studied the anti-diabetic effect of the aqueous, ethanolic and methanolic extracts of Stevia rebaudiana and Phyllanthus amarus on streptozotocin induced diabetic rats. The ethanolic and methanolic extracts of Stevia rebaudiana, has significantly reduced the blood glucose levels than the aqueous extracts. Similarly the methanolic and aqueous extracts of Phyllanthus amarus, has significantly reduced the blood glucose levels than the ethanolic extract.